2022
DOI: 10.1002/ange.202217071
|View full text |Cite
|
Sign up to set email alerts
|

Iron Nanoparticles Protected by Chainmail‐structured Graphene for Durable Electrocatalytic Nitrate Reduction to Nitrogen

Abstract: The electrochemical nitrate reduction reaction (NO 3 RR) is an appealing technology for regulating the nitrogen cycle. Metallic iron is one of the well-known electrocatalysts for NO 3 RR, but it suffers from poor durability due to leaching and oxidation of iron during the electrocatalytic process. In this work, a graphenenanochainmail-protected iron nanoparticle (Fe@Gnc) electrocatalyst is reported. It displays superior nitrate removal efficiency and high nitrogen selectivity. Notably, the catalyst delivers ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Thus, on one hand, ammonium is beneficial for plant nutrition. On the other hand, the application of ammonium only to plant cells leads to extremely quickly uptake and nitrogen overloading [ 34 , 35 , 36 , 37 ]. Several recent investigations have suggested that nitrogen signaling is directly linked with auxin signaling [ 38 , 39 ] and epigenetic modifications [ 36 ].…”
Section: Major Aspects Of Plant Regenerationmentioning
confidence: 99%
“…Thus, on one hand, ammonium is beneficial for plant nutrition. On the other hand, the application of ammonium only to plant cells leads to extremely quickly uptake and nitrogen overloading [ 34 , 35 , 36 , 37 ]. Several recent investigations have suggested that nitrogen signaling is directly linked with auxin signaling [ 38 , 39 ] and epigenetic modifications [ 36 ].…”
Section: Major Aspects Of Plant Regenerationmentioning
confidence: 99%
“…Changes in the microenvironment also have a tremendous regulatory effect on the catalytic performance of materials. [33][34][35] Therefore, we also manipulate the microenvironment by reducing the N atoms around TiFe atoms, thereby exploring the inuence of the microenvironment on the catalytic performance of TiFe/g-C 3 N 4 . As shown in Fig.…”
Section: No 3 Rr Performance For M1m2/g-c 3 Nmentioning
confidence: 99%
“…With the large-scale discharge of industrial wastewater and unreasonable use of fertilizers, nitrate (NO 3 – ) has seriously polluted water resources. Effective conversion of NO 3 – helps to solve the problem of environmental pollution and produce products with utilization value. Due to the low N–O dissociation energy and high solubility, NO 3 – could be reduced to ammonia (NH 3 ) through eight-electron transfer and the conversion efficiency mainly depends on the reaction rate and selectivity. Electrocatalytic nitrate reduction reaction (EC-NITRR) is considered as a green route to the selective hydrogenation of NO 3 – , but the mismatch between the surface reaction rate and the diffusion rate of NO 3 – significantly limits the actual performance of the EC-NITRR system. , Inspired by traditional sewage treatment, the adsorption can promote the concentration of substrate on the surface of catalyst, which would be a feasible approach to address the limitations of surface reaction rate of EC-NITRR. , …”
Section: Introductionmentioning
confidence: 99%